Oil and Gas 2 Student's Book - Naunton J. Jon (Oxford English for Careers)
gives you the language, information, and skills you need to start your career. Learn the English you need to do the job, practise language in real work situations, and learn specialist vocabulary on every page: It's my job - real people talk about their work in a variety of oil and gas careers. Professional skills - key skills for effective communication in the workplaceReading bank - extra practice in reading for oil and gas British and American English terms defined throughout Online interactive exercises to revise and recycle language: www.oup.com/elt/oefc http://www.oup.com/elt/oefc> The Teacher's Resource Book provides everything you need to teach English for oil and gas with confidence: Background information and specialist knowledge of the subject